Examining advanced nursing practice in Hong Kong and Guangzhou - Chun Ki Chun; Frances KY. Wong; Shao Ling Wang; Weiju Chen (Elsevier, 2021)
Objective: There were studies evaluating advanced nursing practice independently in the mainland and Hong Kong Special Administrative Region of China, but there was no attempt to make a comparison of practice between them. This study employed a case study method to examine and compare advanced nursing practice in Hong Kong and Guangzhou. Method: Purposive sampling method was used to recruit 24 advanced practice nurses (APN) who came from the specialty of medical, surgical and pediatric in Hong Kong and Guangzhou. A questionnaire survey and semi-structured interview were conducted to solicit quantitative and qualitative data for exploring the structure-process-outcome of advanced nursing practice. The structure component explored the factors influencing advanced nursing practice. The process part examined APN role components and illustrations of exemplary advanced nursing practice. The outcomes described outcome indicators that best reflected advanced nursing practice. Findings: Findings revealed that in the structure domain, APN education and career development, team approach in healthcare, and support from management, physicians and professional associations were important contextual factors for APN development in both cities. For the process domain, participants had at least 80% of their time practicing independently/interdependently and were engaged in APN activities including direct/indirect patient care, research/project work, initiation of staff and patient protocols. All participants demonstrated competencies with impacts on patient, service and profession in their description of exemplary practice. Participants from both cities ranked patient-related outcomes as top indicators for their advanced nursing practice. Conclusion: This study has revealed that APNs in Guangzhou and Hong Kong shared similar work involvement and impacts and their demonstrated competencies were on par with international counterparts. Continued efforts need to be put in establishing formal APN education, clear clinical career pathway and title protection to empower nurses to provide optimal care to the fullest extent that they are prepared for.